MODIFIKASI PERILAKU DALAM MENURUNKAN PERILAKU KECANDUAN GAME ONLINE PADA SISWA RETARDASI MENTAL RINGAN - Melda Sofia; Herawati Herawati; Kurnia Rahmayanti (JOURNAL OF HEALTHCARE TECHNOLOGY AND MEDICINE, 2025)
Online gaming addiction is a state of dependence on technology in the form of online games that can cause many consequences for the individual concerned, including students with mild mental retardation. Students with mild mental retardation are expected to have the academic skills of a 6th grader by their late teens and can live successfully in society, both independently and with supervision. This research is a qualitative case study of children who have been classified as mild mental retardation. This study used self-management behavior modification to be able to control students' activities in their daily activities. The results showed that the results of the intervention of students' behavior playing games on their mobile phones decreased. Based on these results, it indicates that intervention with self-management can effectively change student behavior to reduce gaming behavior.